If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(8 + 7h) + 2 = 0 (8 * -4 + 7h * -4) + 2 = 0 (-32 + -28h) + 2 = 0 Reorder the terms: -32 + 2 + -28h = 0 Combine like terms: -32 + 2 = -30 -30 + -28h = 0 Solving -30 + -28h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + -28h = 0 + 30 Combine like terms: -30 + 30 = 0 0 + -28h = 0 + 30 -28h = 0 + 30 Combine like terms: 0 + 30 = 30 -28h = 30 Divide each side by '-28'. h = -1.071428571 Simplifying h = -1.071428571
| 9x+9=3y+6 | | 9+9x=6+3y | | 3ab-ab= | | 2x-=3 | | 3y+6=9x+9 | | -9(-9+3j)= | | 6x+y+8x+2y=180 | | -2(a+1)-3(1-7a)=-24 | | 6x+y+8x+2y=0 | | 2x+4x+6x-2(x+3)=34 | | 6(2j+1)+7= | | 8+4x=5x+4 | | -1+5(x+2)=12x+3-17x | | X+3x+2x+3(x+1)=30 | | 5-16=8.5 | | 3x-6y+9= | | 3(4+10x)+x= | | 8x+4x=5x+4 | | x^4-4x^3-x^2+16x=0 | | 2x-3(-5x+8)=17x-2+8 | | 5(a+4)-6a+1=12 | | -8(y+2)-16=16 | | -1+5(x+2)=12x+3-1x | | 3y^4-13y^2-10=0 | | 28+2x-1=3x+22 | | 19.5(13.3-4.4x)=7.2(0.8x-116) | | 4(5t+10)= | | t^4+21t^2+20=0 | | t^4+21lt^2+20=0 | | 6z-12= | | 4(3x-1P)=2(x+3) | | 4(a+2)-9=11 |